Control of iron stress in water-saturated tidal land using ameliorant and its impact on rice productivity - Wahyuni Lestari; Ghulamahdi, Munif; Purwono (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2023)
Fe stress is a problem in swamp lands that reduces the growth and yield of rice. Providing various types of ameliorants and selecting rice varieties are considered an effort to obtain high rice productivity in tidal land. The research aimed to study the effect of various ameliorants on rice growth and production, and to obtain high productivity of tolerant variety to iron stress at different locations of tidal land. The research was conducted in Karya Bakti Village (1°10'34.8